2009
DOI: 10.1016/j.ijgo.2009.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with positive margins in patients with cervical intraepithelial neoplasia grade 3 and postconization management

Abstract: LEEP, carcinoma in situ, menopausal status, and larger area of lesion are risk factors for positive margins. For women with CIN 3 and positive margins, follow-up at an interval of 6 months or repeat excision are treatment options. However, when repeat excision is technically impossible, whether simple hysterectomy or radical surgery is a rational treatment option requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 17 publications
10
30
0
Order By: Relevance
“…They also showed that the need for multiple sweeps during LEEP was the most important predictor of disease persistence [24]. We know that LEEP is associated with higher rates of positive surgical margin in lesions involving more than two-third of the cervix compared to cold-knife conization [25]. As an indicator of number of sweeps, the number of fragments of LEEP was not associated with surgical margin positivity in our study.…”
Section: Discussionsupporting
confidence: 44%
“…They also showed that the need for multiple sweeps during LEEP was the most important predictor of disease persistence [24]. We know that LEEP is associated with higher rates of positive surgical margin in lesions involving more than two-third of the cervix compared to cold-knife conization [25]. As an indicator of number of sweeps, the number of fragments of LEEP was not associated with surgical margin positivity in our study.…”
Section: Discussionsupporting
confidence: 44%
“…After multivariate analysis, both the size of the abnormal TZ and the excisional technique were identified as the two factors having a significant and independent impact on the risk of involved resection margins. Thus, consistent with a previous study [25], the probability of negative margins was significantly higher among patients who underwent CNC. This is likely to be explained by the ability of CNC to simultaneously achieve significantly deeper and larger excision and therefore a higher excised volume.…”
Section: Discussionsupporting
confidence: 92%
“…However, others have found that the resection margin of CIN lesions produced by LEEP, cold knife, or laser was demonstrated to be able to aid in predicting the subsequent recurrence of CIN 3 [7,8]. According to Chen et al, the persistence/recurrence rate of margin-positive cases, 33% (47/141 cases), was significantly higher than that of the margin-negative cases, 2% (21/972 cases) (p \ 0.0001 by Fisher's exact test).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the median follow-up period was not reported in their analysis. The long-term cumulative persistence/recurrence rate, the most important outcome measure of conservative treatment for any pre-malignant lesions, was demonstrated in their report; however, the rate was not compared by the status of their resection margin data, which has been demonstrated elsewhere to be of significant value for the prediction of the outcome of conization procedures for CIN 3 [7,8]. In our present study, the long-term outcome of CIN 3 treated by Shimodaira-Taniguchi conization in our facility was re-analyzed by the status of their resection margins.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation